Pore structure development during hydration of tricalcium silicate by X-ray nano-imaging in three dimensions. (10th March 2019) - Chen, Bo; Lin, Wei; Liu, Xianping; Iacoviello, Francesco; Shearing, Paul; Robinson, Ian
Highlights: Pore structure development of a hydrating C3 S was revealed by X-ray Nano-CT; The shape, size/volume and spatial distribution of the pores was revealed in 3D; The sealed pores grow larger and the open pores become smaller during the hydration. Abstract: Tricalcium silicate (C3 S) is the most important component among the four main clinker phases of Portland cement. Pure C3 S is widely used as a simplified model system of cement in various researches. However, the spatial structure development of cement, even pure C3 S during hydration at the nano-scale has been rarely directly reported. In this work, X-ray nano-computed tomography (X-ray Nano-CT), a non-destructive X-ray analytical method, was used to study the hydration of a pure C3 S sample with a water/C3 S mass ratio of 0.5. The three-dimensional (3D) structure of the hydrating C3 S specimen was investigated to see the internal pore structure evolution within the hardened C3 S paste. Investigation of the 3D structural development of the C3 S specimen at different hydration times was performed to monitor the changes of pore shapes and sizes/volumes. It is found that volumes of the sealed pores generally grow larger, and the open pores become smaller while the volume and the external morphology of the whole hardened C3 S paste remains almost the same during hydration.